2011
DOI: 10.1183/09031936.00039011
|View full text |Cite
|
Sign up to set email alerts
|

Selected clinical highlights from the 2010 ERS Congress in Barcelona

Abstract: This article reviews a selection of presentations at the 2010 annual meeting of the European Respiratory Society held in Barcelona, Spain, which was the largest congress ever in the field of respiratory medicine. The best abstracts from the groups of the Clinical Assembly (Clinical Problems, Rehabilitation and Chronic Care, Imaging, Interventional Pulmonology, Diffuse Parenchymal Lung Disease, and General Practice and Primary Care) are presented in the context of the current literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It seems that primary screening for airflow obstruction with a handheld spirometer prior to full spirometry testing, which is easy to carry-out in all settings, could be considered as an efficient way to screen or find new COPD cases. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…It seems that primary screening for airflow obstruction with a handheld spirometer prior to full spirometry testing, which is easy to carry-out in all settings, could be considered as an efficient way to screen or find new COPD cases. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis showed that assessing three simple variables (age, smoking intensity and smoking status) among patients with any kinds of acute respiratory infections attending urgent primary care could be a feasible and effective way to short-list those who need spirometry testing to confirm the presence of underlying COPD. Moreover, preliminary screening for airflow obstruction using a handheld spirometer prior to full spirometry testing may be an efficient way of finding new COPD cases [29]. …”
Section: Discussionmentioning
confidence: 99%